Gutless - Deuker, Carl (Houghton Mifflin Harcourt, 2016)
When Brock Ripley is cut from the varsity football team because he shies away from physical contact, he loses his friendship with star quarterback Hunter Gates. Now a target for bullying, Brock struggles to overcome his fears and discover his own courage, especially when his friend Richie Fang is bullied by Hunter and things spiral dangerously out of control.